A Psychometric Analysis of the School Success Profile 2020 Microthreat Scale Using Modern Measurement Theory Methods - Gerald J. Bean; Natasha K Bowen (International Journal of School Social Work, 2024)
Objective: Microthreatening behaviors are often prevalent in school settings and can accumulate to create an array of negative impacts on students and staff. There is a substantive need for a scale that can help to measure student perceived microthreats. The primary aim of this study was to examine the psychometric properties of one such scale—the SSP 2020 Microthreat Scale—using modern measurement theory methods. Method: Data used in this study were collected from sixth through ninth grade students in three schools in in the southeastern region of the United States. Schools were using the SSP 2020 compendium to gain a better understanding of their students' strengths and needs and to guide intervention choices. Results: We examined evidence for the adequacy of internal structure of the scale using CFA methods and assessed the reliability and precision of estimated scale scores using IRT methods. Further, we examined scale correlational relationships with other important conceptually related constructs. Scale performance in each of these areas was acceptable. Conclusion: These findings substantively contribute to the validity argument supporting the use of Microthreat Scale in schools. Further research is needed to examine how key factors and characteristics—e.g., gender, race, socioeconomic status, and cultural heritage—could drive differences in how students perceive microthreats.
Keywords: Modern measurement theory; item response theory; confirmatory factor analysis; psychometrics; microaggression; microthreats